Vaginal birth after multiple caesarean section: a case report from India - Shamrao Ramji Wakode; Sakshi Pramod Sharma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Lower segment caesarean sections increase the possibility of maternal morbidity. Hence, since last few decades, initiative for trial of labor after caesarean delivery is being encouraged in selected cases. Accordingly, a 23-year-old fifth gravida, who had a history of previous three lower segment caesarean sections and one vaginal birth approached for delivery service and plan for her vaginal delivery was made after thorough examination and evaluation. A live female child of 3100 grams was delivered following episiotomy. In post-partum period, it was observed that uterus was involuted on abdominal examination and uterine contours were regular in ultrasonography. As the evidences for practice of vaginal delivery in women who underwent 2 or more previous LSCS are still fewer, this report intends to highlight the possibility of successful vaginal birth after multiple caesarean sections.